Electron transport of chemically treated graphene quantum dots-based dye-sensitized solar cells - Mahalingam S.; Manap A.; Rabeya R.; Lau K.S.; Chia C.H.; Abdullah H.; Amin N.; Chelvanathan P. (Elsevier Ltd, 2024)
The main aim of this work is to elucidate the effect of the chemical treatment of titanium tetrachloride (TiCl4) in graphene quantum dots (GQDs)-based dye-sensitized solar cells (DSSCs). Although this type of chemical treatment has been used in DSSCs, the detailed electron transport properties of TiCl4-treated TiO2/GQDs+dye have not been studied yet. In this study, we have proposed a detailed mechanism for how the extra titania layer with TiCl4 provides high surface area and porosity to improve the adsorption of GQDs and dye. Moreover, the electron transport analysis revealed that the treatment reduced the electron recombination rate and increased the electron injection efficiency up to 73.8%, leading to a high Jsc and longer electron lifetime in the DSSC. Additionally, a performance comparison study with other types of GQDs under TiCl4 treatment was also investigated in this work. 2022 Elsevier Ltd